Electronic collaboration in strategic decision-making processes: An application in a global leading company - (:unkn) unknown (IGI Global, 2014)
The pace of change in information and communication technology has accelerated rapidly in the past decade, providing various opportunities for companies to improve their efficiency and competitiveness and also collaborate with their business partners. In the digitally connected 21st century business environment, collaboration among organizations requires electronic communications within and across fields to facilitate superior outcomes. The proper use of technology enables businesses to be more efficient. E-collaboration has been a great tool to improve business and a strategic weapon to change the traditional business relationships. E-collaboration aims to facilitate coordination of decision-making processes, and it is no longer a source of competitive advantage, but instead a competitive necessity. Tightly linking information technology with strategy formulation is one of growing importance in organizations. This chapter aims to explore the role and benefits of technology in decision-making processes by presenting a successful implementation of electronic collaboration in a leading global supplier of electronics and electrical materials and provide useful information to managers and practitioners. © 2014 by IGI Global. All rights reserved.